PENGEMBANGAN MODEL PERMAINAN PASS AND GO BASKETBALL DENGAN DOUBLE HOLES TARGET DALAM PENJASORKES PADA SISWA KELAS V SD NEGERI SIWALAN KECAMATAN GAYAMSARI KOTA SEMARANG TAHUN AJARAN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study to generate Development Model Pass And Go Basketball Game with Double HolesTarget Penjasorkes Elementary School Fifth Grade students Siwalan Gayamsari District Semarang AcademicYear 2013/2014 ". The data was collected using a questionnaire derived from expert evaluation, as well as theuse of field observations obtained from the students. from the test results obtained by a small group of expertevaluation data, which experts Penjas 80% (good), 76% of experts first learned (good), a second study 72%(good), the results of the pilot questionnaire small average psychomotor aspects groups of 86, 96%, 80.95%cognitive, affective aspects of 90.71%, and the average results of the questionnaire at the end of a small group oftest results obtained 86.20% (very good). and the average yield of the final questionnaire large group testingresults obtained 87.33% (very good) .From the above data it can be concluded that the results of field trials thatare classified both models pass and go the basketball game with two holes targets can be used in SD GayamsariSemarang District Siwalan.